Resolving Disputes Arising from Land Acquisition for Public Purposes Involving Indigenous Peoples in the Nusantara Capital Region - Iwan Permadi; M. Hamidi Masykur; Herlindah Herlindah; Setiawan Wicaksono; Md Yazid Ahmad (Faculty of Law, Universitas Negeri Semarang, Indonesia, 2024)
This research endeavors to investigate the intricate process of dispute resolution pertaining to conflicts that emerge between indigenous communities inhabiting the candidate site for the State Capital (Nusantara Capital City) and the Nusantara Capital Authority, a ministry-level institution endowed with the responsibility of overseeing regional administration within the Nusantara Capital City. Spanning an expansive 256,142 hectares of land, the Nusantara Capital City landscape harbors a mosaic of 17 indigenous communities in North Penajam Paser Regency and 34 indigenous communities in Kutai Kertanegara Regency, collectively comprising over 20,000 members, as documented by the Indigenous Peoples Alliance (Aliansi Masyarakat Adat). The procurement of land for the Nusantara Capital City's expansion has engendered protracted conflicts, notably pertaining to the resettlement of indigenous communities and the determination of suitable compensation areas. These conflicts persist without the presence of regulatory safeguards that could protect the rights and interests of indigenous communities while satisfying the exigencies of Nusantara Capital City development. The Indigenous Peoples Draft Law, despite its relevance, fails to address the intricacies of resolving disputes arising from land acquisition for public purposes. Similarly, the existing frameworks for land acquisition designed for public interest do not adequately address conflicts involving indigenous communities that lack legal recognition. Consequently, this research endeavors to propose a comprehensive conflict resolution framework rooted in the fundamental human rights of indigenous peoples, while also accommodating the imperatives of developmental investment. This approach seeks to strike a harmonious balance between the preservation of indigenous rights and the fulfillment of Nusantara Capital City's development needs.